Pembrolizumab-induced agranulocytosis in a pulmonary pleomorphic carcinoma patient who developed interstitial lung disease and ocular myasthenia gravis. Issue 11 (22nd October 2018) - Tozuka, Takehiro; Sugano, Teppei; Noro, Rintaro; Takano, Natsuki; Hisakane, Kakeru; Takahashi, Satoshi; Tanaka, Toru; Kashiwada, Takeru; Takeuchi, Susumu; Kunugi, Shinobu; Minegishi, Yuji; Saito, Yoshinobu; et al.
Abstract: An 82-year-old man with a recurrence of pulmonary pleomorphic carcinoma was treated with pembrolizumab. He achieved partial response after three cycles of pembrolizumab. However, he developed febrile neutropenia. A bone marrow aspiration sample revealed a decrease of mature neutrophils, and anti-neutrophil antibody was detected in blood. Computed tomography scans revealed consolidation in the right lung. Pathological findings in lung biopsy tissue revealed organizing pneumonia. Pembrolizumab-induced agranulocytosis and interstitial lung disease (ILD) were diagnosed. We initiated antibacterial therapy and granulocyte colony-stimulating factor (G-CSF). The neutrophil count immediately increased, and the fever decreased. The improvement of ILD was achieved without using systemic steroids. Moreover, the patient developed ocular myasthenia gravis induced by pembrolizumab. This is the first case report of pembrolizumab-induced agranulocytosis. Agranulocytosis was improved by administration of G-CSF without using systemic steroids. However, further studies are needed to determine the optimal treatment for patients with anti-neutrophil antibody whose tumor has progressed.